11q+10-q=

Simple and best practice solution for 11q+10-q= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11q+10-q= equation:


11q+10-q=0

We simplify the equation to the form, which is simple to understand
11q+10-q=0

We move all terms containing q to the left and all other terms to the right.
+11q-1q=0-10

We simplify left and right side of the equation.
+10q=-10

We divide both sides of the equation by 10 to get q.
q=-1

See similar equations:

| 49x^4+91x^3y-14x^2y^2=0 | | 12-13u=2 | | -8m-7m=0 | | 6-(9/7)n= | | 2.7q-5.8-4.2q=-2.5q-2.9 | | (5y+6)-(3+4x)=10 | | ex-2=3z | | 3.02+2.51x=1.85 | | 7-4(2x-8)=-9 | | (2x-9)/3=8-3x | | w/3-6=-8 | | 8x+6x-3= | | -5n+n=8 | | 5x-13=-x-(-3x+7) | | 604+2.1(z-2)=8.5 | | 12t+6=-7 | | 2t-12-3t= | | 12+6(2x-2)=-13 | | 2c+12=6 | | 2x+3(x+2)=8 | | w/3-6= | | -5=1/4(4+20r)-8r | | -9p+1=-80 | | 7-1.5x=3 | | p+14=12p+24 | | 23-5(10x+9)=-5 | | -9a-7a= | | b/7-4=-5 | | a^4b-ab^3= | | -31=-2x+3 | | 21=4x-9-1x | | a+14=8 |

Equations solver categories